2011
DOI: 10.1038/ejcn.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

Maternal weight misperceptions and smoking are associated with overweight and obesity in low SES preschoolers

Abstract: Objectives: To identify modifiable risk factors for obesity among low socioeconomic status (LSES) children. Methods: Cross-sectional data were obtained from 238 4-7-year-old children and 224 mothers from LSES preschools. Anthropometric measurements were obtained; mothers were interviewed about sociodemographic characteristics, health behaviors, perceptions and beliefs. Results: The combined prevalence of overweight and obesity (OWOB) among children was 29.8% based on the new World Health Organization (WHO) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
14
1
Order By: Relevance
“…A study by Chen et al (2017) also reported that maternal belief about their child's risk for obesity is associated with higher child BMI. Existing literature states that parents who accurately perceive their child's weight are more likely to be motivated to change their health-related behaviours (Kaufman-Shriqui et al 2012;Mareno 2014). Furthermore, parents' perceptions of child weight influence their feeding style such as imposing restrictions that are positively related to child BMI (Nowicka et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Chen et al (2017) also reported that maternal belief about their child's risk for obesity is associated with higher child BMI. Existing literature states that parents who accurately perceive their child's weight are more likely to be motivated to change their health-related behaviours (Kaufman-Shriqui et al 2012;Mareno 2014). Furthermore, parents' perceptions of child weight influence their feeding style such as imposing restrictions that are positively related to child BMI (Nowicka et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings in children are consistent with those of Raum et al who found a greater BMI at the age of 6 in offspring of mothers who smoked both in the first year of life and currently, independent of maternal smoking before or during pregnancy [ 17 ]. Kaufman-Shriqui and colleagues [ 28 ] reported an association between current maternal smoking and overweight or obesity in a small sample of lower socioeconomic Israeli children aged 4 to 7 years. Florath and colleagues [ 23 ] demonstrated a significant association between current maternal smoking and the BMI of 8 year old German children, and a slightly larger association between paternal smoking and BMI in the same sample.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a larger health promotion intervention study examining low socioeconomic status (SES) preschoolers in Israel . Participants were recruited from September through November 2008 using the local municipality and Ministry of Education's list of 24 low SES preschools to which admission is dependent on family income.…”
Section: Methodsmentioning
confidence: 99%